Crime and environment. Analysis of facilities as crime risk factors in Niš, Serbia - Stanković Dušan (Archiwum Kryminologii, 2020)
This study aimed to examine the relationship between environmental facilities as risk factors and crime. Police data of property and violent criminal offences registered during 2018 in the city of Niš, Republic of Serbia, has been geocoded. Grid cells of 100 by 100 meters were designed as spatial units for the analysis, and geoinformation data of 12 different facilities were extracted from GIS. The negative binomial regression model was constructed to investigate crime risky facilities. The crime is mostly related to facilities as banks and exchange offices, bus stops, gyms and recreational centers. On the other hand, cafes, nightclubs, and big shopping centers were not significantly associated with crime. Finally, limitations, practical and theoretical usage of the research are discussed.